2020
DOI: 10.18280/ts.370503
|View full text |Cite
|
Sign up to set email alerts
|

A New Early Stage Diabetic Retinopathy Diagnosis Model Using Deep Convolutional Neural Networks and Principal Component Analysis

Abstract: Diabetic retinopathy (DR) is a disease of the retina, which leads over time to vision problems such retinal detachment, vitreous hemorrhage, glaucoma, and in worse cases leads to blindness, which can initially be controlled by periodic DR-screening. Early diagnosis will lead to greater control of the disease, whereas performing retinal examinations on all diabetic patients is an unattainable need, as diabetes is a chronic disease and its global prevalence has been steadily increasing over the past few decades.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Pretrained versions of these networks on comprehensive public datasets like ImageNet [10] can be directly applied to tasks with labels overlapping with the original dataset or indirectly via transfer learning when labels differ. CNNs have been employed for image classification and object detection across various domains, including medical image classification [11,12], plant disease recognition [13][14][15], face recognition [16], and document classification [17,18].…”
Section: Related Workmentioning
confidence: 99%
“…Pretrained versions of these networks on comprehensive public datasets like ImageNet [10] can be directly applied to tasks with labels overlapping with the original dataset or indirectly via transfer learning when labels differ. CNNs have been employed for image classification and object detection across various domains, including medical image classification [11,12], plant disease recognition [13][14][15], face recognition [16], and document classification [17,18].…”
Section: Related Workmentioning
confidence: 99%
“…This model predicted DR with an accuracy of 95% [23]. Mohammed Hasan et al, suggested a combined method of Convolution Neural Network and Principal Component Analysis for the diagnosis of DR with an accuracy of 98.44% [24]. Hemelings et al, suggested a method based on a deep learning approach to identify glaucoma in which the fundus image was cropped with radius as image size percentage, optic nerve head (ONH) centered with spacing of 10-60%.…”
Section: Related Workmentioning
confidence: 99%
“…Salama and Aly [20] obtained an accuracy of 98.87% with the U-Net model and InceptionV3 with the data augmentation for the breast cancer classification. Data augmentation influences the average precision of the class [21][22][23]. In the classification of mixed gases, Han et al [24] used VGG16, VGG19, ResNet18, ResNet34, and ResNet50 and achieved an accuracy of 96.67% with the adjustment of parameters.…”
Section: Related Workmentioning
confidence: 99%